Peningkatan Unjuk Kerja Pada Link Microwave Menggunakan Teknik Diversity Maximal Ratio Combining - Mudhoep, Debbi Irfan; Sari Hartati, Rukmi; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2020)
In communication systems using microwave waves (microwave links), the presence of noise and multipath fading can reduce and reduce the performance of communication systems. Microwave propagation is influenced by several things in the reception system besides having to LOS (Line of Sight) there is a reflected signal from the surface that is causing interference (multipath signal). By using the diversity maximal ratio combining technique on systems affected by noise and fading, it is used through BER (Bit Error Rate) analysis. The use of research simulations to determine the improvement of the system at the recipient by comparing before and after using the maximal ratio combining technique